Averaging effect on improving signal reproducibility of gap-based and gap-free SERS substrates based on ordered Si nanowire arrays. Issue 9 (17th January 2017) - Huang, Jian-An; Zhao, Yingqi; Zhu, Xiaoyue; Zhang, Wenjun
Abstract : A gap-free SERS substrate was found to achieve both high reproducibility and high enhancement against the reproducibility/enhancement trade-off in gap-based substrates. Abstract : While the surface-enhanced Raman spectroscopy (SERS) technique has the merit of an inherent ultrahigh sensitivity, low signal reproducibility due to nonuniformities in SERS substrates is a challenge to be considered for its practical applications. Utilizing averaging effects to improve the signal reproducibility can be achieved by either increasing hot spot density on the SERS substrates or using large laser spots to enlarge the probing area. However, mechanisms of how the averaging effects overcome the nonuniformities and improve the reproducibility remain unclear. Herein, we use ordered SERS substrates with designed gap-based and gap-free electric fields in the hot spots to systematically study the mechanisms. Our result suggests that the highest reproducibility comes from the gap-free hot spots that depend on the least parameters. In contrast to the gap-based substrate with a trade-off relation between reproducibility and enhancement, the gap-free substrate exhibits both high reproducibility and high enhancement. Our findings clarify the contributions of the SERS substrate to the averaging effect and could pave the way to the design of reproducible SERS substrates for further practical applications.